Evaluasi Pengelolaan Limbah Medis Padat di Puskesmas Mattirobulu Kabupaten Pinrang - Majid, Makhrajani; Nurpaisa A, Nurpaisa A; Zarkasyi R, Rahmat; Nuddin, Andi; Herlina, Herlina (Jurnal Ilmiah Manusia Dan Kesehatan, 2024)
Complex issues exist in the handling of medical waste at health centers. The Ministry of Environment and Forestry's statistics reveals that solid medical waste management is still subpar since only 26.8% of Community Health Centers have incinerators, while the remaining 73.2% lack these facilities. This study's objective was to evaluate the Mattirobulu Health Center's solid medical waste management procedure utilizing a descriptive research design and qualitative methodology. The research tools included in-depth, organized interviews, documentation, and field observations. From February to March 2023, it will be executed. The survey target was the Puskesma manager as the main informant, the environmental health manager as the main informant, then the environmental health officer/Sanling as the supplementary informant, and the cleaning service as the additional informant. The results showed that the solid medical waste disposal system was not properly and accurately implemented, as evidenced by personal protective equipment (PPE) still being basic and improperly used, the lack of color-coded plastic waste bags in each service unit during the sorting phase, the storage tanks that were still very small during the storage phase, and the medical waste transport process through non- medical Temporary Storage Areas (TPS) where there was no dedicated route and empty space..